Effects of some Peruvian non-distilled alcoholic beverages on dental erosion - Monica Quispe-Zuta; Franz Coronel-Zubiate; Henry Zelada-Romero; Carlos Farje-Gallardo; Tania Castillo-Cornock; Paola La Serna-Solari; Heber Arbildo-Vega (Universidad de Concepción., 2021)
Objective: To determine the erosive effect of pieces of permanent teeth exposed to non-distilled alcoholic beverages. Material and Methods: This study takes a quantitative approach, with an explanatory scope, descriptive and correlational, with a pure experimental design. The sample consisted of 45 premolar permanent teeth, which were randomly allocated to five sample groups. Every sample group was submerged in dark beer Cuzqueña Negra, wheat beer Cuzqueña de Trigo, lager beer Cerveza Cristal, lager beer Pilsen Callao and physiological saline solution; every solution had a quantity of 110 mL. The experiment was performed for five minutes, with three repetitions every 12 hours over a period of 70 days. The sampling was performed every seven days, using an analytical scale and a data sheet. Results: The average weight loss of dental pieces put in dark beer Cuzqueña Negra (pH 4.0) was 239.4456 mg. In lager beer Pilsen Callao (pH 4.6), it was 146.7867 mg. In lager beer Cerveza Cristal (pH 3.7), it was 131.3567 mg. In wheat beer Cuzqueña de Trigo (pH 4.5), it was 121.7122 mg. Lastly, in physiological saline solution (pH 6.8), it was 14.3311 mg. When applied to the sample, the statistical test Student's t-test resulted in a value of p≈0.000 (p<0.05). Conclusion: Non-distilled alcoholic beverages caused erosive effects in the pieces of permanent teeth.